Epidemiology and care management of Paroxysmal Nocturnal Hemoglobinuria (PNH) in a real-world setting in France: Description from the French National Hospitalization Database - Régis Peffault de Latour; Sophie Pibre; Julien Vercruyssen; Marie Laetitia Desjuzeur-Bellais; David Pau; Stève Bénard; Louis Chillotti; Nathalie Grandfils (PLoS ONE, 2026)
Introduction Paroxysmal nocturnal hemoglobinuria (PNH) is a rare, acquired stem-cell disease causing anemia, aplasia and thromboses, affecting ~1/80,000 patients in France. Treatment mainly involves C5 inhibitors (C5i) and iterative red-blood-cell transfusions. Recent real-world French data on PNH epidemiology and management are scarce in the era of complement inhibitors. This study described PNH epidemiology, patients’ characteristics, and C5i use. Methods This was a non-interventional claims study using secondary data from the French national hospital database. Patients with a hospital diagnosis of PNH (ICD-10 code D59.5) over 2018–2022 were selected, after exclusion of those with other C5i-treated diseases. A subgroup of C5i initiators was followed from initiation to last hospitalization, to describe C5i treatment patterns. Results The study included 897 patients: 496 (55.3%) receiving a C5i and 218 (24.3%) initiating treatment over 2018–2022. In 2022, 725 PNH patients were identified (prevalence ~1/94,000). Mean (SD) age was 52.1 (21.1) and 45.7 (19.4) years overall and among C5i initiators, respectively. C5i initiators had 20.9 (6.9) dispensations annually. Most patients initiated with eculizumab (n = 196, 89.9%), and almost half of them (n = 80, 40.8%) switched to ravulizumab. Conclusion PNH prevalence was ~ 1/94,000. Most patients initiated eculizumab, with 40.8% switching to ravulizumab.